The impact of dance on the mental health of older adults: a network meta-analysis of anxiety, depression, and well-being - Zhang, Yuexin; Ma, Hongtao (Frontiers in Psychology, 2025)
ObjectiveThis systematic review and meta-analysis (PROSPERO CRD420251015051) compared the effects of nine distinct dance interventions on the mental health of older adults.MethodsSix databases were searched from the earliest records to April 2025. Studies investigating a dance intervention lasting≥4 weeks, including Mental Health and cognitive function health outcomes. Two independent reviewers performed literature screening and data extraction. Review Manager 5.4 was used for pairwise meta-analyses and risk of bias assessment, while Stata 18.0 software was employed for network meta-analyses.ResultsOf 269 records identified, 13 studies met the inclusion criteria. Total sample size of included studies was 1,083 (females, males). The results of the traditional meta-analysis showed that Chinese square dance was superior to the control group in alleviating depression (SMD = 1.11, 95% CI: 0.48, 1.75). For well-being, Chinese square dance was superior to the control group in enhancing well-being (SMD = −1.98, 95% CI: −2.55, −1.41). For anxiety, Chinese square dance was superior to the control group in alleviating anxiety (SMD = 1.21, 95% CI: 0.65, 1.76). For cognitive function, no significant differences were found. In the network meta-analysis, the ranking of treatment effects for depression showed that dance games > Chinese square dance > rhythmic gymnastics > Turkish folk dance > Poco dance > ballroom dance > aerobic dance > control group> creative dance. The ranking of treatment effects for well-being showed that Chinese square dance > aerobic dance > Turkish folk dance > control group. The ranking of treatment effects for anxiety showed that Chinese square dance = group dance > Poco dance > control group, while for cognitive function, the ranking showed Poco dance > Chinese square dance > creative dance > control group.ConclusionThis study found that dance has positive effects on improving depression and anxiety whilst enhancing well-being among older adults. Among the nine different types of dance interventions, it was considered an effective approach for improving depression, well-being, and anxiety. However, we encourage older adults to choose dance modalities that suit their interests to enhance adherence.